2015
DOI: 10.1021/jacs.5b09152
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxidation by the [Co4O4(OAc)4(py)4]+ Cubium is Initiated by OH Addition

Abstract: The cobalt cubium Co4O4(OAc)4(py)4(ClO4) (1A(+)) containing the mixed valence [Co4O4](5+) core is shown by multiple spectroscopic methods to react with hydroxide (OH(-)) but not with water molecules to produce O2. The yield of reaction products is stoichiometric (>99.5%): 41A(+) + 4OH(-) → O2 + 2H2O + 41A. By contrast, the structurally homologous cubium Co4O4(trans-OAc)2(bpy)4(ClO4)3, 1B(ClO4)3, produces no O2. EPR/NMR spectroscopies show clean conversion to cubane 1A during O2 evolution with no Co(2+) or Co3O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(119 citation statements)
references
References 77 publications
6
110
2
Order By: Relevance
“…Previous computational and in situ or ex situ spectroscopic studies during catalytic alkane hydroxylation and water oxidation reactions mediated by non-haem cobalt catalysts, including cobalt–oxygen clusters (for example, Co x O y ), have frequently proposed Co IV –O species as the active oxidants that effect the stereospecific C–H activation and O–O bond formation reactions2021222324252627282930. However, despite the ubiquity of putative Co IV –O intermediates in cobalt-catalysed redox reactions, direct spectroscopic characterization of the Co IV –O species under catalytic conditions has been achieved in only extremely rare cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous computational and in situ or ex situ spectroscopic studies during catalytic alkane hydroxylation and water oxidation reactions mediated by non-haem cobalt catalysts, including cobalt–oxygen clusters (for example, Co x O y ), have frequently proposed Co IV –O species as the active oxidants that effect the stereospecific C–H activation and O–O bond formation reactions2021222324252627282930. However, despite the ubiquity of putative Co IV –O intermediates in cobalt-catalysed redox reactions, direct spectroscopic characterization of the Co IV –O species under catalytic conditions has been achieved in only extremely rare cases.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, owing to their importance in a plethora of oxygen-dependent processes, inorganic compounds containing terminal metal–oxo moieties have been discussed or sought for this curious class of LTMOs19, which are thought to be reactive intermediates in a number of oxygen-dependent processes. Of particular relevance to this study are the cobalt(IV)–oxo species, which have also been proposed as reactive intermediates in a number of cobalt-mediated oxidation reactions2021222324252627. In particular, for catalytic oxidation of water to give molecular oxygen, a topic of intensive research aimed at developing artificial photosynthesis and efficient water splitting catalysis, ex situ electron paramagnetic resonance (EPR)28, X-ray absorption29 and time-resolved Fourier-transform infrared30 spectroscopic methods have provided direct evidence for the involvement of terminal and bridging cobalt(IV)–oxo species as key intermediates in the water oxidation reactions.…”
mentioning
confidence: 99%
“…In a very recent study, Dismukes and coworkers suggested that O-O bond formation involving a [Co 4 O 4 ] 5+ -based "cubium" happens via geminal coupling of two terminal oxo ligands on the same Co center. 75 This event is preceded by partial removal of a bridging bidentate acetate ligand and attack of hydroxide. Their inspiring study certainly motivates future research into the catalytic mechanism of 1, for which we have already computationally investigated ligand mobility of bridging, as well as monodentate acetate.…”
Section: Scheme 2 Oxo-oxo Coupling Pathwaymentioning
confidence: 99%
“…814 Functional models that are structurally similar to the OEC, or to an active site of an oxide catalyst, are far more rare. Only recently was the catalytic edge site of the layered oxide–hydroxide CoOOH successfully modeled by the molecular tetracobalt oxido cubane Co 4 ( μ 3 -O) 4 (OAc) 4 py 4 , to reveal a surprising mechanism for OER that implicates an unusually high formal oxidation state for cobalt.…”
Section: Introductionmentioning
confidence: 99%